2018
DOI: 10.1016/j.bios.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid aptamer-based methods for diagnosis of infections

Abstract: Infectious diseases are a serious global problem, which not only take an enormous human toll but also incur tremendous economic losses. In combating infectious diseases, rapid and accurate diagnostic tests are required for pathogen identification at the point of care (POC). In this review, investigations of diagnostic strategies for infectious diseases that are based on aptamers, especially nucleic acid aptamers, oligonucleotides that have high affinities and specificities toward their targets, are described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 140 publications
1
81
0
1
Order By: Relevance
“…This is partially because most aptamers are currently selected against cancer biomarkers. However, the scope of application should extend to other diseases, such as neurodegenerative and infectious diseases, as the number of aptamers identified each year increases [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…This is partially because most aptamers are currently selected against cancer biomarkers. However, the scope of application should extend to other diseases, such as neurodegenerative and infectious diseases, as the number of aptamers identified each year increases [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we immobilized short DNA oliguncleotides (aptamers) to reduced graphene oxide film through a modified EDC/HNS reaction. Aptamers as biosensitive agents have such advantages over antibodies as higher stability, much simpler and cheaper synthesis [10][11][12][13][14]. As a final point we demonstrated selective response of sensors structures based on reduced graphene oxide with the binded aptamers to the target and reference proteins.…”
Section: Introductionmentioning
confidence: 79%
“…Compared with antibody, aptamers are less labor‐intensive and more easily labeled with enzymes, biotin, fluorescent dyes, and DNA ligands. Besides, the function of immobilized aptamers can be easily regenerated and aptamers can be reused (Park, 2018). It has been reported that biosensors based on aptamers possess outstanding features, such as high affinity, selectivity, stability, and productivity (Verdian, 2017).…”
Section: Future Prospects and Technical Challengesmentioning
confidence: 99%